2016
DOI: 10.1523/jneurosci.4660-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Correlations in Primary Visual Cortical Neurons Driven by Fixational Eye Movements

Abstract: The ability to distinguish between elements of a sensory neuron's activity that are stimulus independent versus driven by the stimulus is critical for addressing many questions in systems neuroscience. This is typically accomplished by measuring neural responses to repeated presentations of identical stimuli and identifying the trial-variable components of the response as noise. In awake primates, however, small "fixational" eye movements (FEMs) introduce uncontrolled trial-to-trial differences in the visual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 59 publications
(16 reference statements)
2
25
0
Order By: Relevance
“…9G). Consistent with previous results (Martinez-Conde et al, 2000), we observed a significant modulation in firing rates around the time of these small eye movements (Fig. 9G, orange is the control MU firing rate aligned to randomly shuffled microsaccades).…”
Section: Detection Performance Versus Single-trial Spike-time Correlasupporting
confidence: 92%
See 1 more Smart Citation
“…9G). Consistent with previous results (Martinez-Conde et al, 2000), we observed a significant modulation in firing rates around the time of these small eye movements (Fig. 9G, orange is the control MU firing rate aligned to randomly shuffled microsaccades).…”
Section: Detection Performance Versus Single-trial Spike-time Correlasupporting
confidence: 92%
“…Next, we examined the effects of small eye movements on our MU responses. During a trial, small eye movements such as microsaccades can modulate neural activity in area MT (Herrington et al, 2009) and areas that drive MT such as V1 (Snodderly et al, 2001;McFarland et al, 2016), which could introduce spike-time correlations between our two MT sensory pools. We extracted the occurrence of putative microsaccades as shown by the example trial in Figure 9F (asterisks indicate that three saccades in the 300 ms analysis window aligned the motion pulse; see Materials and Methods).…”
Section: Detection Performance Versus Single-trial Spike-time Correlamentioning
confidence: 99%
“…Using awake and task-engaged monkeys eliminates this confound and ensures that collective fluctuations, which introduce uncontrolled factors into the measured correlations, are minimized . Eye movements have been shown to contribute to correlations in the visual cortex (McFarland et al, 2016). In our case monkeys were rewarded to fixate on a spot at the center of the screen during the presentation of off-foveal stimuli and trials in which fixation could not be maintained were removed from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fixational eye movements, also called micro-saccades, have been reported to modulate neuronal activity in the visual system, 38,39 contribute to neuronal response variability, 40,41 and act as an index of the focus of covert spatial attention based on subtle changes in their directionality with attention condition. 42 Given these findings, we considered two means by which micro-saccades could account for our results.…”
Section: Resultsmentioning
confidence: 99%